Caribbean Report 09-03-1999 - The British Broadcasting Corporation; Ransome, Debbie (anchor, correspondent); Liverpool, Anthony 'Mamba' (interviewee); Richards, Ken (correspondent); Fleming, Osbourne (interviewee); Fergus, Howard (interviewee); Paeman, Hugo (interviewee); Morgan, Tabitha (correspondent); Reynolds, Paul (correspondent); Burns, Larry (interviewee) (The British Broadcasting Corporation, 1999)
1. Headlines with anchor Debbie Ransome (00:27) 2. The polls close in Antigua/Barbuda national elections as forty two candidates contest seventeen seats in the House of Representatives. The Antigua Labour Party lead by Prime Minister Lester Bird is seeking its fifth consecutive term against opposition leader Baldwin Spencer United Progressive Party. Debbie Ransome interviews journalist Anthony ‘Mamba’ Liverpool on voter turnout and the electoral process. Ken Richards reports on the Antigua Sun newspaper ongoing dispute and industrial action by workers on the paper’s support for the governing Antigua Labour Party (00:28 – 05:00) 3. In Anguilla, Hubert Hughes takes the oath of office as Chief Minister having won at the polls in the recently concluded Anguilla elections. Coalition partner Victor Banks is sworn in as Finance Minister. Anguilla United Party and Anguilla Democratic Party together won four of the seven seats contested. Opposition leader Osbourne Fleming Antigua National Alliance won two seats. Osbourne concedes defeat and discusses future transformation of his party (05:01 - 06:31) 4. The island of Montserrat is in the process of reforming the electoral system as the eruption of the Soufriere volcano led to four constituencies covered in ash, the evacuation of thousands of citizens and relocation of the remaining population to the northern part of island. Howard Fergus the Head of a three man election commission reports on tasks assigned to assess new constituencies and recommend a new voting system Montserratians living abroad to vote (06:32 - 08:47) 5. A war of words continue in the stalemate banana trade war between the European Union (EU) and the US. EU ambassador to Washington Hugo Paeman assures of continuing preferential treatment for Caribbean bananas. Banana planters in Caribbean and Latin America await WTO ruling as the banana industry supports their economy. Tabitha Morgan interviews farmers in Jamaica. Correspondent in Washington Paul Reynolds analyses the banana trade dispute from ...